Perioperative Outcomes, Complications, and Efficacy of Robotic-Assisted Prolapse Repair: A Single Institution Study of 196 Patients. Issue 6 (November 2018) - Gupta, Priyanka; Ehlert, Michael; Bartley, Jamie; Gilleran, Jason; Killinger, Kim A.; Boura, Judith A.; Nagaraju, Pradeep; Fischer, Melissa
Introduction: Abdominal pelvic organ prolapse repair is efficacious for uterovaginal and apical prolapse. We describe the safety and efficacy of robotic prolapse repair in a large teaching institution. Methods: Consecutive robotic-assisted prolapse repairs at a single institution between 2006 and 2014 were retrospectively reviewed for patient characteristics, operative information, and outcomes. Results: A total of 196 women (mean age, 61 ± 9 years) underwent robotic prolapse repair (189 sacrocolpopexy, 6 sacrohysteropexy, 1 enterocele repair). Concomitant procedures included hysterectomy (88), midurethral sling (84), and/or Burch colposuspension (7). Mean odds ratio time was 242 ± 69.9 minutes, and median length of stay was 1 day. Intraoperative complications were as follows: cystotomy (4), vaginotomy (4), conversion to open (2), bowel injury/aborted (1), adhesions/aborted (1), and ureteral injury (1). Women with complications had greater blood loss than those without complications ( P = 0.0015). Immediate (<30 days) postoperative complications were rare: port-site hernia (2), discitis (1), ileus (1), and ulnar neuropraxia (3). At median follow-up of 9 months (range, 0–85 months), 14 women had recurrent grade 3 prolapse, and 4 had grade 2 apical prolapse. Nine of 14 women had additional prolapse repair at a mean of 9.5 ± 6.3 months. Vaginal mesh exposure was detected in 12 (6.3%) of 192 women. There were 6 procedures for mesh exposure and 2 procedures for exposed sutures. One mesh erosion into the bladder required open excision. Conclusions: In this large series of robotic prolapse repair, complications are infrequent. Short-term apical outcomes are excellent. Few women required additional compartment repairs within 1 year with 6% rate of mesh exposure. Abstract : In this large series of robotic prolapse repair, we examine outcomes and complications; short-term apical outcomes are excellent, and complications are infrequent.